Nanoantenna-assisted plasmonic enhancement of IR absorption of vibrational modes of organic molecules - Milekhin, Alexander G.; Cherkasova, Olga; Kuznetsov, Sergei A.; Milekhin, Ilya A.; Rodyakina, Ekatherina E.; Latyshev, Alexander V.; Banerjee, Sreetama; Salvan, Georgeta; Zahn, Dietrich R. T. (Beilstein Journal of Nanotechnology, 2017)
Nanoantenna-assisted plasmonic enhancement of IR absorption and Raman scattering was employed for studying the vibrational modes in organic molecules. Ultrathin cobalt phthalocyanine films (3 nm) were deposited on Au nanoantenna arrays with specified structural parameters. The deposited organic films reveal the enhancement of both Raman scattering and IR absorption vibrational modes. To extend the possibility of implementing surface-enhanced infrared absorption (SEIRA) for biological applications, the detection and analysis of the steroid hormone cortisol was demonstrated.
Keywords: cobalt phthalocyanine; cortisol; localized surface plasmon resonance; metal nanoantennas; Raman scattering; surface-enhanced infrared absorption (SEIRA)